Fundamental of Entrepreneurship (ENT300) : Shoes deluxe shop (SDS) / Sharifah Nurnatasha Wan Badwie … [et al.] - Wan Badwie, Sharifah Nurnatasha; Ganding, Bethysia Lindy; Umbom, Beckclean Manyie; Abu Samah, Syazwan; Roja, Ryron (2014)
SHOES DELUXE SHOP (SDS) is given name an idea of company partnership. Shoes Deluxe Shop (SDS) was established on 1 January 2015. This new baby born company possesses the new outcomes of shoes. Shoes Deluxe Shop is a shoes shop which display variety kind of shoes which have many types of colours, sizes, patterns and designs. We provide a variety of shoes for all types off people either man or woman.Shoes Deluxe Shop is located at The Summer in Desa llmu Kota Samarahan, Sarawak. The idea of starting the business came from the observation of the range of the target market that we will have since the many housing, universities and colleges. There are UNIMAS, UI TM, IPG, Secondary and Primary school and many more. There are many students and the workers which we choose as a target market.